Exploring Thematic Structures and Progression in Self-Help Literature: A Textual Metafunction Analysis of “The 5 Second Rule” - Putri, Gusti Agung Mira Diana; Ayomi, Putu Nur (Journal of Language and Literature Studies, 2024)
Given the widespread appeal and influence of self-help literature, understanding how authors engage and inform their readers through linguistic strategies is crucial. The study aims to explore how thematic structures contribute to the genre’s purpose of motivating and guiding readers. A descriptive qualitative method was employed, involving observation, interpretation, and explanation. The analysis reveals that the most frequent Themes in the text are Unmarked Topical Themes, primarily in the forms of “You,” “I,” and “It.” The text also frequently utilizes Conjunctive Adjuncts as Textual Themes (e.g., "First," "Second") and Modal Adjuncts as Interpersonal Themes. The zig-zag pattern emerged as the dominant Thematic Progression, allowing the author to maintain clarity and engagement. The strategic use of Theme and Mood facilitates an approachable, mentor-like voice, helping to establish a connection with the reader. These findings offer valuable insight into how thematic structures and progression are employed in self-help literature to enhance readability, coherence, and emotional engagement. The study contributes to a deeper understanding of the linguistic mechanisms that drive the effectiveness of self-help texts in fulfilling their social and communicative purposes.